The Role of Gender on HIV/AIDS Stigma among Medical Students in Puerto Rico: Implications for Training and Service Delivery - Varas-Díaz, Nelson; Neilands, Torsten B.; Cintrón-Bou, Francheska; Santos-Figueroa, Axel; Rodríguez-Madera, Sheilla; Santiago-Negrón, Salvador (Puerto Rico Health Sciences Journal, 2012)
Objective: This study aimed to assess the role of gender on HIV/AIDS stigma among 507 medical students in Puerto Rico. Methods: A secondary data analysis was performed with baseline measurements of a controlled randomized study. Results: Unadjusted analyses showed that the overall multivariate test for gender was significant [χ2(11) = 38.79, p = .0001]. Males evidenced higher stigma levels on multiple dimensions of HIV/AIDS stigma. Conclusion: Findings suggest that gender needs to be taken into consideration when engaging in stigma research and when developing stigma reduction interventions as part of medical students training.